Upaya Optimalisasi Kinerja Pegawai Koperasi Serba Usaha (KSU) Padurenan Jaya Kudus Melalui Holiday Exchange - Qomar, Moh Nurul; Praatmana, Nanang Dwi (BISNIS, 2019)
This article discusses human resource management approach Koperasi Serba Usaha (KSU) Padurenan Jaya  so that the optimization of employee performance can be achieved. The approach in question is a holiday exchange. This study uses a qualitative method with a field research approach. The results of this study indicate that the holiday exchange approach applied at KSU Padurenan Jaya has proven to be able to improve services to members and increase the cooperative business results (SHU). The application of this system is also in accordance with Islamic business ethics, which refers to the value of unity and responsibility so that it affects the flexibility of management in determining holidays.